Evaluating Potential Bias through Analyzing Patterns in Use of the ‘Smell of Alcohol’ in Prehospital Medicine Patients with Altered Mental Status across Various Demographic Groups - Hyde, Andrew; Rouillard, Christopher (International Journal of Paramedicine, 2025)
“Smell of alcohol” (SoA) is widely used as a diagnostic tool. However, assigning SoA to a patient is entirely provider dependent and may be associated with negative social connotations. This paper aims to identify differences in the diagnostic application of SoA among patients in the prehospital setting. We further investigate whether SoA impacts patient care by evaluating transport times. To accomplish these aims, we performed a cross-sectional study of the National Emergency Medical Services Information Service (NEMSIS) databases for 2017-2023. SoA was established using NEMSIS’s standardized substance use evaluation metric. In part one of our study, we analyzed the use of SoA across multiple demographic factors including race and ethnicity, age, and gender. We found statistically significant differences in the application of the SoA metric to non-White patients (OR 1.056, 95% CI 1.052-1.060 to 1.266, 95% CI 1.248-1.283). Similar patterns were observed in the application of ‘Other Substance Use Suspected’ to Black or African American (OR 1.217, 95% CI 1.213-1.221) and female (OR 1.133, 95% CI 1.130-1.136) patients. In part two of our study, we observed increased transport times for patients with a confirmed alcohol level. No increase was observed in patients with a positive SoA. These results suggest that SoA is applied in a biased manner across demographics, but its application does not influence patient transportation time in the prehospital setting.